IMF Staff Papers, Volume 49, No. 3. (IMF Staff Papers; IMF Staff Papers ;, 2002)
This paper empirically investigates the monetary impact of banking crises in Chile, Colombia, Denmark, Japan, Kenya, Malaysia, and Uruguay during 1975-98. Cointegration analysis and error correction modeling are used to research two issues: (i) whether money demand stability is threatened by banking crises; and (ii) whether crises lead to structural breaks in the relation between monetary indicators and prices. Overall, no systematic evidence that banking crises cause money demand instability is found. The paper also analyzes inflation targeting in the context of the IMF-supported adjustment programs.